Microwave enhanced processing of ores - Kobusheshe, Joseph (2010)
Recent research developments have suggested that microwave assisted comminution could provide a step change in ore processing. This is based on the fact that microwave-absorbent phases within a multi-mineral ore can be selectively heated by microwave energy hence inducing internal stresses that create fracture.